Bicycle Traffic Flow Forecasting Methodology for Different Functional Zones of The City - Miglė Zabielaitė-Skirmantė; Marija Burinskienė (The Baltic Journal of Road and Bridge Engineering, 2025)
The development of bicycle transport infrastructure, like any other, must be based on expected bicycle traffic flow data. The characteristics of the city’s functional zones, as well as the presence of existing bicycle infrastructure, determine the choice to travel by bicycle. Existing bicycle traffic flow forecasting methodologies are characterised by complex calculations, specific software, and the need for abundant data. Therefore, there is a clear need for a simpler bicycle flow forecasting methodology that specialists responsible for urban development would be able to use and which could be applied in practice, when designing bicycle infrastructure. Taking this into account, the article analyses the methodologies for predicting bicycle traffic flows for the central and middle zones of the city, created on the basis of a sketch plan methodology, when the infrastructure designed in the middle zone connects and does not connect to the general bicycle network. To determine the precision of the presented methodologies, field studies of bicycle traffic flows were carried out at three locations in the city of Vilnius. The study found that all the examined methodologies were accurate, since the MAPE of the central zone was 17.61%, the MAPE of the middle zone, when the planned infrastructure connects to the general bicycle network – 15.03%, and the MAPE of the middle zone, when the planned infrastructure does not connect to the general bicycle network – 13.85%. The predicted bicycle traffic flows calculated using the methodologies presented in the article can be used when it is necessary to decide what type of bicycle infrastructure to choose or what width of technical parameters of bicycle paths to choose.